THE EFFECT OF POSITIVE-NEGATIVE AFFECT, AUTOMATIC THOUGHTS AND OTHER PERSONAL VARIABLES UPON THE INNOVATION MANAGEMENT SELF-EFFICACY BELIEF LEVELS OF SCHOOL ADMINISTRATORS - Murtezaoglu, Serkan; Yuksel-Sahin, Fulya (GAZIOSMANPASA UNIV, 2018)
This study aims to examine how innovation management self-efficacy belief levels of school administrators are influenced by positive or negative affect, positive or negative automatic thoughts, gender, marital status, education level and seniority. The study sample consists of 304 school administrators. Positive and Negative Affect Schedule, Automatic Thoughts Questionnaire, Scale for Innovation Management at Schools and Personal Information Form were employed for data collection. The collected data were analyzed by MANOVA, Games-Howell Test, Tukey Test and t-test. The results revealed significantly higher levels of innovation management self-efficacy beliefs among the single administrators with positive affect, positive automatic thoughts and less seniority. On the other hand, no significant difference was found according to gender and education level.
Keywords: Positive or Negative Affect; Automatic Thoughts; Innovation Management; Administrators; AFFECT SCHEDULE; VALIDITY; RELIABILITY; HEALTH; PANAS; Psychology